Optimalisasi Rancangan Desa Pintar melalui Peningkatan Literasi Kewargaan Karang Taruna di Bidang Penangkalan Berita Palsu: Optimizing the Smart Village Design by Increasing Karang Taruna’s Civic Literacy in Preventing Fake News - Mawarti, Rista Ayu; Hanafi, Hanafi; Agung, Laksamana Prammana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
This study aims to describe the stages and analyze the impact of training to increase Karang Taruna civic literacy in preventing fake news in Wonokerso Village. This training is part of optimizing the Smart Village design which is a program of Wonokerso Village. The method used is community empowerment with a participatory approach, including needs identification, planning, implementation, and evaluation. The results of the study show that, first, the training was successfully implemented by community empowerment theory which opened up opportunities to increase the youth's understanding of civic literacy, especially in identifying and preventing fake news. Second, the impact of this training can be seen in the increase in the active participation of youth organizations in village activities, especially as the front guard in disseminating accurate and reliable information to the community. These findings confirm that to realize the smart village concept, the civic literacy of village residents is something that cannot be ignored by the government.